Power Relations and Self-Transformation in Bucha (2024) - Andika Prasetyo; Much. Koiri (CV. Ulil Albab Corp, 2026)
The Russo-Ukrainian war that sparked since 2014 has triggered a national turmoil that affects the Ukrainian film industry. In the context of contemporary Ukrainian cinema, the ongoing Russo-Ukrainian war with the indication of the presence of the Russian Armed Forces in Ukrainian soil, has allowed Ukraine to produce films and documentaries depicting resistance and the bravery of Ukrainian society towards the enemy of oppression. Following the journey of the main character, Kostia, in an attempt to rescue Ukrainian citizens of Bucha from the grasp of the Russian Armed Forces, Bucha (2024) becomes a film where Kostia acquires his self-transformation journey due to the presence of power relations. Using the visual and textual analysis of the selected scenes and dialogues in the film, curated by Foucault’s power relations and Nietzsche’s self-transformation concepts, this study discovered that in Bucha (2024), power relations specifically tied to the Kostia are manifested through mind and body, and has caused Kostia to have consciousness of old values (camel phase), evoking resistance to the oppression (lion phase), and defining his new values (child phase).